The Relationship Between Knowledge And Attitudes Of Young Women Towards Self-Breast Examination (Sadari) - Nanin Juliana; Lindawati Lindawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Breast cancer can attack anyone, especially women, women's attitudes and awareness regarding breast health are still not well developed so that most cancer cases are found at an advanced stage, when early stage healing is very easy, and can be done at home. Just a few minutes, once a month, to do a breast self-examination. The research aims to determine the relationship between knowledge and attitudes of young women towards breast self-examination (BSE) at SMA Negeri 14 Medan City, North Sumatra Province in 2023. The conceptual framework used is based on dependent and independent variables. The research design is correlational. The research was conducted February 23-25 ​​on 88 respondents. The research data were analyzed manually and using frequency distribution tables. Based on attitudes, out of 35 (100%), the majority of young women have negative attitudes and do not carry out conscious examinations. namely 35 (67.3%) people and a minority of young women who have negative attitudes and have carried out self-breast examinations. 17 (32.7%) P value = 1.000. It can be concluded that there is no relationship between young women's attitudes towards breast self-examination (BSE). For young women, it is hoped that every young woman will be responsive to changes, or the presence of lumps and pain that are felt or arise in the breasts. For health institutions, it is hoped that they can provide counseling and information so that young women are motivated to be able to routinely carry out self-examination of their breasts and teach the techniques and appropriate time to do it.